2021
DOI: 10.1101/2021.10.11.21264744
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early intervention with a glycerol throat spray containing cold-adapted cod trypsin after self-diagnosis of the common cold: a randomised prospective, parallel group and single-blind methods trial (Glycerol-cod trypsin spray in common cold)

Abstract: Background: A glycerol throat spray containing cold-adapted cod trypsin (GCTS) deactivates common cold virus in vitro and decreases pharyngeal rhinovirus load after inoculation in humans. We relied on early self-diagnosis and evaluated two different scales to detect a treatment effect in naturally occurring common colds. Methods: Adults were enrolled in this randomised, prospective, parallel group, single-blind study to begin treatment six times daily at first sign of a common cold or were assigned to a non-t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 34 publications
4
9
1
Order By: Relevance
“…The study found that ColdZyme was able to reduce the duration of the common cold, symptom severity ratings, and the associated number of missed training days. Lastly, the safety and tolerability of ColdZyme shown in previous trials [13][14]19 has now been confirmed in a large study population.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…The study found that ColdZyme was able to reduce the duration of the common cold, symptom severity ratings, and the associated number of missed training days. Lastly, the safety and tolerability of ColdZyme shown in previous trials [13][14]19 has now been confirmed in a large study population.…”
Section: Discussionsupporting
confidence: 55%
“…The common cold started with a similar mean burden of symptoms in the two groups, with a Jackson score of 7.3 ± 3.6 (mean and standard deviation, SD) for the ColdZyme group and 7.1 ± 3.7 for the placebo group on the evening of Day 1, which was similar to the previous single-blind trial (7.5 in the treated group). 14 The common cold was confirmed by a blinded investigator within three days from the start of a perceived common cold at Visit 2 in 98.2% of the subjects in the ColdZyme group and 99.1% in the placebo group, with no statistically significant difference.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations